51 Neointimal tissue coverage and characterization assessment using optical coherence tomography surveillance six months after implantation of bioresorbable scaffolds versus conventional everolimus eluting stents in ISAR-absorb MI trial. (30th September 2020) - Rai, H; Alfonso, F; Maeng, M; Bradaric, C; Wiebe, J; Cuesta, J; Christiansen, E-H; Harzer, F; Cassese, S; Hoppmann, P; Colleran, R; Schneider, S; et al.
Abstract : Background: Bioresorbable scaffolds (BRS) were introduced to overcome the limitations of permanent metallic stent implantation. Optical coherence tomography (OCT) can provide important insights on vessel wall healing at follow-up. We compared OCT-assessed healing at 6 months after implantation of everolimus-eluting BRS and everolimus-eluting metallic stents (EES) in patients treated for acute myocardial infarction (AMI). Methods: ISAR-Absorb MI is a multicentre, 2:1 randomized trial comparing outcomes of patients with AMI stented with BRS or conventional EES. Angiographic surveillance was planned for all patients at 6–8 months follow-up; surveillance with OCT at follow-up was discretionary. For the present analysis, patients with OCT follow-up were included and images analyzed at a core laboratory. Tissue characterization using grey-scale signal intensity (GSI) analysis was done for neointimal regions of interest (ROI) with thickness of 100 to 400 µm. ROI's were classified as mature using a cut-off GSI score of 109.7. Generalized linear mixed model was used as appropriate. Results: 70 patients in the BRS arm and 32 patients in the EES arm had OCT available for analysis at a median follow-up of 216 days. Minimum lumen area [5.13 (3.95, 6.70) vs. 4.93 (3.84, 6.99) mm 2 ] and minimum stent area [5.78 (4.88, 7.34) vs. 6.39 (4.77, 7.45) mm 2 ] were comparable between BRS and EES. In total 2, 237 frames with 19, 827 struts were assessed. Overall strut coverage was better with BRS compared to EES (97.5% vs. 90.9%, p<0.001), while malapposed struts (1.1% vs. 0.5%, p=0.51) were more common with EES. Neointimal coverage was comparable in both stent groups [85.5 (61.9, 124.1) vs. 69.5 (32.7, 127.5) µm in BRS and EES groups, p=0.20]. GSI analysis in 95 cases showed that immature ROIs were numerically more common in the EES group as compared to the BRS group (75.4 vs. 57.0%; p=0.35). Conclusions: In selected patients undergoing OCT imaging at 6–8 months after implantation of BRS and conventional EES for AMI, we observed generally favorable healing characteristics with high rates of strut coverage and fewer areas of immature neointimal areas with BRS in comparison to EES.